Artocarpus altilis extract effect on cervical cancer cells - Abdul Jamil, Muhammad Mahadi; Ganeson, Suhassni; Mammam, Hassan Buhari; Abdul Wahab, Ridhwan (Elsevier B.V, 2018)
This paper elucidate on the effects of Artocarpus Altilis Pulp part on cervix HeLa cancer cell. IC50 values of pulp extract were determined on HeLa cell with different concentration (12.5µg/ml, 25µg/ml, 50µg/ml, 100µg/ml). Cell viability and cell growth were observed up to 72 hours with comparative to control cells. The results obtained in this research quantitatively revealed the dependence of cell proliferation on extract concentration. Control, 12.5µg/ml, 25µg/ml, 50µg/ml, 100µg/ml of concentration showed 100%, 90%, 80%, 50%, 44% cell viability after 72 hours in culture respectively. This study result demonstrates that Artocarpus Altilis has the ability to inhibit cervical cancer cell proliferation.